2016
DOI: 10.1093/rheumatology/kew262
|View full text |Cite
|
Sign up to set email alerts
|

Interferon α kinoid induces neutralizing anti-interferon α antibodies that decrease the expression of interferon-induced and B cell activation associated transcripts: analysis of extended follow-up data from the interferon α kinoid phase I/II study

Abstract: Objective. IFN α Kinoid (IFN-K) is a therapeutic vaccine composed of IFNα2b coupled to a carrier protein. In a phase I/II placebo-controlled trial, we observed that IFN-K significantly decreases the IFN gene signature in whole blood RNA samples from SLE patients. Here, we analysed extended follow-up data from IFN-K-treated patients, in order to evaluate persistence of neutralizing anti-IFNα Abs antibodies (Abs), and gene expression profiling.Methods. Serum and whole blood RNA samples were obtained in IFN-K-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…We have not been able to test these molecules in any monogenic interferonopathy. Interestingly, inactivated interferon α 2b coupled to a carrier protein can induce the production of a polyclonal antibody response against all 13 subtypes of interferon α, and a reduction of the associated interferon signature in high responders to vaccination (Ducreux et al, 2016). These data link nicely with those showing that patients with mutations in AIRE produce endogenous antibodies against all interferon α subtypes, but not interferon β, γ, or λ (Meyer et al, 2016).…”
Section: Cellular Pathology and Therapeutic Approachesmentioning
confidence: 99%
“…We have not been able to test these molecules in any monogenic interferonopathy. Interestingly, inactivated interferon α 2b coupled to a carrier protein can induce the production of a polyclonal antibody response against all 13 subtypes of interferon α, and a reduction of the associated interferon signature in high responders to vaccination (Ducreux et al, 2016). These data link nicely with those showing that patients with mutations in AIRE produce endogenous antibodies against all interferon α subtypes, but not interferon β, γ, or λ (Meyer et al, 2016).…”
Section: Cellular Pathology and Therapeutic Approachesmentioning
confidence: 99%
“…Indirectly inhibiting the type 1 interferon pathway by means of an IFNα kinoid (IFN-K) vaccine has also been studied in patients with SLE. This vaccine comprises IFNα2b coupled to a carrier protein, which together induce native, polyclonal neutralizing anti-IFNα antibodies 82 . Interferon α kinoid induces neutralizing anti-interferon α antibodies that decrease the expression of interferon-induced and B cell activation associated transcripts: analysis of extended follow-up data from the interferon α kinoid phase I/II study Rheumatology2016; 55(10):1901-5.…”
Section: [H2] Targeting the Interferon Pathwaymentioning
confidence: 99%
“…Mathian et al found that active immunization of human IFN-α transgenic mice with a human IFN-α kinoid (IFN-K) could induce polyclonal neutralizing antibodies against IFN-α, suggesting that IFN-K vaccination may be a promising therapy for SLE [160]. IFN-K vaccine could effectively ameliorate lupus manifestations by inducing neutralizing antibodies in both mouse lupus model and SLE patients [160][161][162][163]. Clinical trials showed that IFN-K was well tolerated and significantly reduced disease activity in SLE patients [163,164].…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%